Unlocking Village Potential: Empowering Tanuharjo Officials to Boost Revenue through Village-Owned Enterprises - Sumarto, Slamet; Martitah, Martitah; Kristiono, Natal; Hidayat, Arif; Putra, Tegar Islami (Universitas Negeri Semarang, 2024)
This study examines the optimization of the role of Tanuharjo Village officials in increasing village revenue through the establishment and management of Village-Owned Enterprises (BUMDes). The creation of BUMDes in Tanuharjo Village has proven to be a strategic initiative to maximize village potential and enhance local economic development. This article provides an overview of the service activities that have been carried out, focusing on the critical role of Tanuharjo Village officials in optimizing village income through the establishment, management, and active participation in BUMDes. The BUMDes has played a vital role in creating new jobs, boosting the productivity of key village sectors, and strengthening the local economy. Additionally, BUMDes serves as a platform for encouraging innovation and the entrepreneurial spirit within the village community. Through one-way counseling sessions organized by the Semarang State University service team, the capacity of Tanuharjo Village officials in BUMDes management has been significantly enhanced. The strategies implemented during these activities included the development of new business units by optimizing village resources, the creation of management training programs to improve BUMDes governance, and digital marketing training for human resources. These efforts have successfully increased the understanding and capabilities of village officials, contributing to improved performance in managing BUMDes and increasing village revenue. This service activity has provided practical recommendations for improving BUMDes governance, which are expected to stimulate further economic growth and improve the welfare of the community in Tanuharjo Village.